Telomeres act autonomously in maize to organize the meiotic bouquet from a semipolarized chromosome orientation - Carlton, Peter M. (The Rockefeller University Press, 2002)
During meiosis, chromosomes undergo large-scale reorganization to allow pairing between homologues, which is necessary for recombination and segregation. In many organisms, pairing of homologous chromosomes is accompanied, and possibly facilitated, by the bouquet, the clustering of telomeres in a small region of the nuclear periphery. Taking advantage of the cytological accessibility of meiosis in maize, we have characterized the organization of centromeres and telomeres throughout meiotic prophase. Our results demonstrate that meiotic centromeres are polarized prior to the bouquet stage, but that this polarization does not contribute to bouquet formation. By examining telocentric and ring chromosomes, we have tested the cis-acting requirements for participation in the bouquet. We find that: (a) the healed ends of broken chromosomes, which contain telomere repeats, can enter the bouquet; (b) ring chromosomes enter the bouquet, indicating that terminal position on a chromosome is not necessary for telomere sequences to localize to the bouquet; and (c) beginning at zygotene, the behavior of telomeres is dominant over any centromere-mediated chromosome behavior. The results of this study indicate that specific chromosome regions are acted upon to determine the organization of meiotic chromosomes, enabling the bouquet to form despite large-scale changes in chromosome architecture.